TI_GERICHTE 15.2016.102 vom 24. Mai 2017 , Minimo di esistenza. Pignoramento di arretrati di rendite AVS versati in capitale - TI Tribunale d'appello (2017)
Minimo di esistenza. Pignoramento di arretrati di rendite AVS versati in capitale